Properties of the thermoplastic starchpolylactic acid blends compatibilized by hyperbranched polyester (2020)
With the aim of to contribute to the employ of new compatibilizing agent and to the preparation of biodegradable materials, in this study were obtained thermoplastic starch/polylactic acid blends and was evaluated the compatibilizing effect of a hyperbranched polyester polyol of second generation modified with polylactic acid in these blends. The blends were prepared in a torque rheometer. In all cases the weight ratio of thermoplastic starch/polylactic acid was 50/50 wt%. The proportions of the compatibility were 5 wt%, 10 wt% 15 wt%, and 20 wt% regard to the total amount of thermoplastic starch and polylactic acid. The blends were characterized by infrared, thermogravimetric, differential scanning calorimetry, X-ray diffraction, scanning electron microscopy and rheological analyses. Torque value decreased with the proportion of compatibilizing. Therefore, the compatibilizing also acted as plasticizing. By infrared analysis was observed that the increasing on the compatibilizing content enhanced the intensity of the signals corresponding to OH and C=O groups. By X-ray diffraction and differential scanning calorimetry analyses was observed a reduction of the crystallinity of the blends obtained with compatibilizing. By rheological analysis was evidenced the formation of a microstructure, which is able to elastically deform.